The Impact of Dose and Simultaneous Use of Acid-Reducing Agents on the Effectiveness of Vemurafenib in Metastatic BRAF V600 Mutated Melanoma: a Retrospective Cohort Study - Knapen, Lotte M. (Target Oncol, 2018)
BACKGROUND: The impact of dose and simultaneous use of acid-reducing agents (ARAs) on the effectiveness of vemurafenib is unknown. OBJECTIVES: To determine the association between progression of metastatic BRAF V600 mutated melanoma and (1) dose reductions of vemurafenib and (2) simultaneous use of vemurafenib and ARAs. PATIENT AND METHODS: A retrospective cohort study of 112 first-line vemurafenib users for melanoma was conducted (March 2012–March 2016), using electronic patient records and pharmacy dispensing records of a Dutch academic hospital. Cox regression analysis was used to estimate the risk of progression with full-dose (n = 64) versus reduced-dose vemurafenib (n = 48) and with simultaneous use of vemurafenib and ARAs (n = 35) versus vemurafenib alone (n = 77). Analyses were adjusted for age and sex. RESULTS: In total, disease progression occurred in 55% of treated patients on vemurafenib, with a median progression-free survival of 6.0 (95% confidence interval [CI] 5.0–6.9) months. Compared to patients on vemurafenib alone, there was no increased risk of progression among patients requiring vemurafenib at a reduced dose or among patients receiving simultaneous therapy with vemurafenib and ARAs. In addition, there was no increased risk of progression among patients who used reduced-dose vemurafenib and ARAs versus those receiving full-dose vemurafenib as sole therapy. However, a tendency for progression was observed among patients who used full-dose vemurafenib and ARAs versus full-dose vemurafenib alone (adjusted hazard ratio [HRa] 2.37; 95% CI 0.97–5.76), which became statistically significant in a sensitivity analysis (HRa 4.56; 95% CI 1.51–13.75). CONCLUSIONS: There was no association between the use of vemurafenib in a reduced dose or the simultaneous use of vemurafenib and ARAs and the risk of progression. In addition, there was no association between the simultaneous use of vemurafenib in a reduced dose and ARAs and the risk of progression. However, patients tolerating  full-dose vemurafenib simultaneously with ARAs might have an increased risk of progression. This finding requires prospective validation. [Image: see text]